2021
DOI: 10.1111/cea.13997
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for persistent symptoms in adults previously hospitalized for COVID‐19

Abstract: Background The long‐term sequalae of COVID‐19 remain poorly characterized. We assessed persistent symptoms in previously hospitalized patients with COVID‐19 and assessed potential risk factors. Methods Data were collected from patients discharged from 4 hospitals in Moscow, Russia between 8 April and 10 July 2020. Participants were interviewed via telephone using an ISARIC Long‐term Follow‐up Study questionnaire. Results 2,649 of 4755 (56%) discharged patients were successfully evaluated, at median 218 (IQR 20… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
129
4
7

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 143 publications
(182 citation statements)
references
References 29 publications
12
129
4
7
Order By: Relevance
“…Long-term health consequences of COVID-19 remain unknown, but reports suggest that prolonged symptom duration and limitations in functioning are common among hospitalised as well as non-hospitalised adults [13,14] and children [15,16]. The spectrum of longlasting symptoms is wide and varies from mild discomfort to severe adverse effects on physical, cognitive, and psychosocial health [17], with important wider implications on functioning, including employment and school attendance.…”
Section: Post-covid Condition Health Consequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-term health consequences of COVID-19 remain unknown, but reports suggest that prolonged symptom duration and limitations in functioning are common among hospitalised as well as non-hospitalised adults [13,14] and children [15,16]. The spectrum of longlasting symptoms is wide and varies from mild discomfort to severe adverse effects on physical, cognitive, and psychosocial health [17], with important wider implications on functioning, including employment and school attendance.…”
Section: Post-covid Condition Health Consequencesmentioning
confidence: 99%
“…Multiple studies from different countries found that many individuals experienced persistent symptoms 6 months after COVID-19, with fatigue or muscle weakness, sleep difficulties, and anxiety or depression among the most common sequelae [13,14,18]. A recent study suggests that although most COVID-19 survivors recover both physically and functionally a year after acute infection, some still experience problems with mobility, pain or discomfort, and anxiety or depression compared with non-COVID-19 controls [19].…”
Section: Post-covid Condition Health Consequencesmentioning
confidence: 99%
“…It should be noted that most studies included samples with <500 participants, were conducted in one single center, included follow-up periods shorter than 12 weeks and did not specifically focus on sex differences [15][16][17][18][19][20][21][22][23][24][25]. Three recent multicenter studies have been published [26][27][28]. Sigfrid et al included 327 hospitalized COVID-19 survivors from five hospitals and reported that females younger than 50 years were two times more likely to report fatigue and seven times more likely to report dyspnea than men of the same age seven months after hospital discharge [26].…”
Section: Introductionmentioning
confidence: 99%
“…Sigfrid et al included 327 hospitalized COVID-19 survivors from five hospitals and reported that females younger than 50 years were two times more likely to report fatigue and seven times more likely to report dyspnea than men of the same age seven months after hospital discharge [26]. Munblit et al included 2649 COVID-19 survivors from four different hospitals and found that female sex was associated with persistent post-COVID symptoms, particularly dermatological changes, seven months after hospitalization [27]. Zhang et al included 2433 hospitalized COVID-19 survivors from two centers and reported that female sex was associated with a higher risk of post-COVID fatigue [28].…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, what are the risk factors for developing long covid? Although some studies in adults have suggested that severity of the initial infection, hospital admission, female sex, white ethnicity, middle age, and asthma are risk factors for persistent symptoms,121011 the most recent and comprehensive meta-analysis concluded that data were insufficient to determine the influence of these factors 3. Secondly, what are the molecular, immunological, and psychological mechanisms underlying long covid?…”
mentioning
confidence: 99%